2010
DOI: 10.1155/2010/793854
|View full text |Cite
|
Sign up to set email alerts
|

Diameter‐Controllable Magnetic Properties of Co Nanowire Arrays by Pulsed Electrodeposition

Abstract: The Co nanowires with different diameters were prepared by pulsed electrodeposition into anodic alumina membranes oxide templates. The micrographs and crystal structures of nanowires were studied by FE-SEM, TEM, and XRD. Due to their cylindrical shape, the nanowires exhibit perpendicular anisotropy. The coercivity and loop squareness (Mr/Ms) of Co nanowires depend strongly on the diameter. Both coercivity and Mr/Ms decrease with increasing wire diameter. The behavior of the nanowires is explained briefly in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
9
2
Order By: Relevance
“…Magnetic metallic wires have received a remarkable interest in the last few years due to their potential applications in devices such as tunable microwave filters [1,2], miniaturized magnetic sensors based on the giant magnetoresistance (GMR) effect [3][4][5] or magnetic recording media with perpendicular-to-plane effective anisotropy [6,7], among others. The implementation of efficient large-scale synthesis methods that allow the mass production of different types of metallic wires in a homogeneous and reproducible manner is essential to cope with the current technological needs in all the aforementioned areas.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Magnetic metallic wires have received a remarkable interest in the last few years due to their potential applications in devices such as tunable microwave filters [1,2], miniaturized magnetic sensors based on the giant magnetoresistance (GMR) effect [3][4][5] or magnetic recording media with perpendicular-to-plane effective anisotropy [6,7], among others. The implementation of efficient large-scale synthesis methods that allow the mass production of different types of metallic wires in a homogeneous and reproducible manner is essential to cope with the current technological needs in all the aforementioned areas.…”
Section: Introductionmentioning
confidence: 99%
“…Pulse plating has been satisfactorily used by several authors to fill all the pores of anodic aluminum oxide (AAO) templates with various metal nanowires (e.g., Ni or Co) [11,12]. During the study of Co [4][5][6][7][13][14][15][16][17][18][19][20], Ni [5,16,19,[21][22][23], and their alloys [24][25][26] it was concluded that the quality of the resulting wires strongly depends on the duty cycle. A relatively long pause between the pulses is preferable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the template-assisted method, ferromagnetic metal is electrodeposited into the template with numerous nanochannels with large aspect ratio (cylinder-like nanopores). This method is a very attractive approach to synthesizing ferromagnetic metal nanowires because it can be carried out using simple experimental devices and its cost is low [6]. Typical template materials include ion track-etched polycarbonate films [7-10] and anodic aluminum oxide (AAO) films [11].…”
mentioning
confidence: 99%
“…As a result, the diameter (d), length (L) and aspect ratio (L/d) of nanowires, which are electrodeposited into nanochannels, can be adjusted. Therefore, many researchers have synthesized ferromagnetic metal nanowire arrays by using the AAO templates [6,[12][13][14][15][16]. In addition, hexagonal close-packed cobalt (hcp-Co) has large magneto-crystalline anisotropy along the c-axis [17,18].…”
mentioning
confidence: 99%